TELAAH RISET ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DI INDONESIA: TINJAUAN SYSTEMATIC LITERATURE REVIEW - Auvi, Rahmatul; Widiastuty, Erna (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
This study aims to synthesize the results of previous research on Environmental, Social, and Governance (ESG) through a systematic literature review (SLR). This study uses SLR to present quantitative data to determine the development of ESG issues. There are several parameters used, namely journal sources, variable mapping and theory as well as fields of science, research approaches, and countries. The results of this study indicate that there were 48 articles originating from international and national reputable journals during the 2010-2023 period. ESG topics related to corporate governance, management and behavior accounting, information systems, auditing, and ethics are researches with ESG issues that are constantly evolving. Stakeholder theory is the most widely used theory and the dominant use of quantitative methods in ESG research. China is a developed country that does a lot of research on ESG issues, while in developing countries most research on ESG is conducted in Malaysia. Based on the ESG measurements that are widely used are the results of measurements issued by Bloomberg. Keywords: ESG, SLR, Voluntary Disclosure